Eating green in Copenhagen: organic consumers’ path to less meat and minimal food waste - Matthiessen, Lea Ellen; Smed, Sinne; Jensen, Jørgen Dejgård; Średnicka-Tober, Dominika; Rossi, Laura; Bügel, Susanne Gjedsted (Frontiers in Sustainable Food Systems, 2025)
IntroductionUnsustainable and unhealthy food consumption is contributing significantly to the global greenhouse gases and leads to severe health problems. The largest contributors are consumers in high-income countries, such as Denmark, with large shares of meat and high amounts of food waste.MethodsTaking Copenhagen (the capital) as a case, we aim to explore more sustainable and healthier dietary behaviours based on the organic food share in combination with dietary composition, food waste and attitudes towards change. This mixed-method study used quantitative data from an anonymous online survey and qualitative data from semi-structured interviews. For statistical analysis, 279 adult survey participants were divided into three subgroups; “low”– with up to 25% organic food share, “medium”– 26-75% organic food share and “high”– 76-100% organic food share.ResultsThis study found significant differences of food intake between the subgroups for fruits & vegetables, legumes, nuts, whole grain cereals and meat. In those food categories, the share of respondents complying with the official dietary recommendations was higher for the “high” and “medium” than for the “low” organic subgroup. At the level of public procurement, meat was reduced to provide “a room for economic manoeuvre” due to higher organic price premiums. In conclusion, in Copenhagen we observed that an increased share of organic food comes along with other sustainable dietary behaviour, both at household and public kitchen level.DiscussionHouseholds appear motivated by societal momentum toward more sustainable diets. The public food procurement has largely been driven by politically determined goals. Further studies are needed to better understand how food systems can support the adoption of healthier, more sustainable diets — emphasizing increased plant-based foods and reduced food waste.